THE EFFECT OF BREASTFEEDING ON THE HEALTH INDICATORS OF YOUNG CHILDREN (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
Promotion and coverage of breastfeeding are considered to be the cost-effective public health measures in terms of Healthcare System. The aim of the research is to assess an influence of breastfeeding on infants’ health and quality of life (QL) parameters. This observational prospective study included 1790 newborns selected from Yerevan State Medical University’s Polyclinics (“Mouratsan”, sample=746, and “Heratsi”, sample=1044). Data collection took a period between January 2016 and December 2017. Evaluation of children’s quality of life was performed with the help of the validated and adapted QUALIN questionnaire. The data related to child’s health condition were collected from the “Child Development History” cards available at the polyclinics of the investigated area. Among 1770 one year old children 1681 were ever breastfed, 1224 (69.1%) were exclusively breastfed up to 3 months, the median duration of breastfeeding was 6–7 months, 45% were breastfed for more than 6 months, and 15% were breastfed for more than 1 year. There is a significant difference between the QL scores of the ever breastfed and the never breastfed subgroups. Duration of the breastfeeding also have an influence on QL scores. The given study’s results confirm that breastfeeding among the early aged Armenian children is of great importance in their health, influencing on quality of life and morbidity rates.
Keywords: breastfeeding; quality of life; QUALIN questionnaire; early aged children